Chronically busy, chronically unhealthy? Understanding the time poverty and health interplay through systematic review synthesis - Sukhpreet Kaur Jaggi; Deepa Jitendra Gupta (Cogent Social Sciences)
The hustle culture of this generation and rising health concerns highlights the urgent need to tackle time poverty as a public health issue. The study breaks down the complexity of time constraints and their health interplay by synthesising the past literature. The study uses the PEO (Population, Exposure, Outcome) search approach to search the Scopus and Web of Science databases. After a thorough review, 16 significant papers were selected. The study deploys a thematic framework and finds central concerns which are caused by time poverty, such as the’cycle of servitude,’ ‘unseen labour’, ‘non-remunerative’, ‘underpaid’. ‘extended workdays’, ‘commute experiences’, and ‘disrupted work’, lead to health issues. The study’s framework is an important link that can help policymakers and future researchers establish health policies based on the challenges addressed in this study.